Rational use of antibiotics – A narrative review (Research, Society and Development, 2022)
Introduction: The advent of antibiotics in the 1940s certainly revolutionized modern medicine and provided modern man with a sense of security regarding the risks facing a bacterial infection. This euphoria, however, was present for a limited period, as the apparent solution to an old problem raised an even greater one – antibiotic resistance. Objectives: to carry out a literature review presenting a relevant discussion about antimicrobial resistance and bring recent evidence regarding the rational use of antibiotics. Methodology: searches were carried out in the Scielo, PubMed and Google Scholar databases, using the keywords: Bacterial Pharmacoresistance, Rational Use of Medicines and Antibiotics. Discussion and conclusion: The rational use of antibiotics is based on a series of basic knowledge that underpins clinical reasoning and allows the assistant to use these drugs more assertively, in order to obtain better results and minimize the risks of their use. In addition to the known adverse effects, the use of these drugs encompasses what has been a worldwide health problem for decades, mainly due to unnecessary, inappropriate or suboptimal use in the case of health professionals. Therefore, the current situation requires the discussion and implementation of measures aimed at regulating the sale and its effective inspection, as well as educating the population and professionals on the subject through constant discussion and updating on the subject.